Functionalization of Single Walled Carbon Nanotubes with Optically Switchable Spiropyrans - PEROVA, TANIA; GIORDANI, SILVIA; DEL CANTO, ELISA; FLAVIN, KEVIN; NATALI, MANUEL (My University, 2010)
The design, synthesis and complete characterization of a smart material composed of single-walled nanotubes functionalized with spiropyran-based photo switchable molecules are reported. The chemical complexity of the system requires the use of a range of complementary techniques in order to provide a complete picture of the composition and performance of the nanomaterial. Thermal gravimetric analysis ensured both the high degree of chemical functionalization and the presence of molecular switches in the nanotube sample; micro-Raman indirectly confirmed the successful oxidation of the tubes, FT-IR proved the nature of the functional groups introduced based on their characteristic stretching vibrations and atomic force microscopy demonstrated nanotube lengths of approximately 600 nm. UV-Vis-NIR absorption spectroscopy was used to evaluate the photoresponsive behaviour of the nanomaterial, and the intensity of the absorption band at 556 nm could be modulated by light-induced reversible conversion of the spiropyran molecules attached to the SWCNT from the spiro close conformation to the merocyanine open form. We were also able to provide the first example of a continuous solution based on-off switching in a spiropyran-nanotube material.
PUBLISHED
Keywords: nanotubes; Nanoscience & Materials